The paradoxical simile, A stylistic feature in the poems of Seyyed Hasan Hosseini and Qeysar Aminpoor - Sayyed Ahmad Parsa; Behnam Bastami (مطالعات زبانی و بلاغی)
The poetry in sixties has some certain features because of the socio-political environment, and especially the war. On one hand, poetry was a reflection of the atrocities of the Ba'athist enemy and on the other hand, it’s the reflection of self-sacrifice and resistance of the people of this country in an unequal battle. The researchers’ too much emphasis on the resistance poetry during this period has led to the marginalization of literary creativity and innovation in these poems. Considering this issue, the present study, investigates a less known type of simile in the poems of Seyyed Hasan Hosseini and Qeysar Aminpour and analyzes it as a stylistic feature. The paradoxical simile, is created through the combination of two concepts of simile and paradox, from two fields of rhetoric and prosody and in terms of structure and usage, there are three categories: The first category, in which tenor and vehicle are two fundamentally contradictory phenomena. The second category is paradoxical in the similarity. In the third category, the vehicle is a paradoxical item by itself and this paradox affects the totality of the simile. Innovation in the imagination by means of reconstruction in the simile format, surprising the audience and forcing him/her to discover the hidden beauty in the simile‚ and challenging the traditional rhetorical boundaries are considered as the characteristics of this sort of simile. The method in this study is descriptive-analytical and the data have been analyzed by using the content analysis method. The results show that the tendency of the poets to the Indian style‚ the conflicts in the society‚ the mental engagement of the poets and other things as so‚ are the main reasons for the creation of these similes.